SIMULATION OF AUTOMATED WATER TREATMENT CONTROL - COSTACHE (BIRA) Lenuta (Fiabilitate şi Durabilitate)
A to optimize the work in wastewater treatment plants can use the automation system consisting the using SIMULINK- MATLAB. The results are very good using FUZZY CONTROLLER if they are programed properly and efficiently. The chosen technology combines natural treatment with biological treatment with activated sludge. This solution the monitoring of the parameters in the purification processes is an essential activity in the wastewater treatment plants significantly reduces electricity consumption and ensures the valorisation of nutrients in wastewater.